Automation of us-datcom lateral stability and control derivatives - 239296 Oon, Kim Ping (Sekudai : UTM, 1996)
Project paper (Bachelor of Mechanical Engineering (Aeronautical)) - Universiti Teknologi Malaysia, 1996